In situ simulation for cardiopulmonary resuscitation training: A systematic review - Andrea Cortegiani; Mariachiara Ippolito; Cristian Abelairas-Gómez; Sabine Nabecker; Alexander Olaussen; Kasper G. Lauridsen; Yiqun Lin; Taylor Sawyer; Joyce Yeung; Andrew S. Lockey; Adam Cheng; Robert Greif; et al. (Resuscitation Plus)
Objectives: To evaluate the effectiveness of in situ simulation for cardiopulmonary resuscitation (CPR) training on clinical and educational outcomes. Methods: Randomised controlled trials (RCT) and non-randomised studies evaluating in situ simulation for cardiopulmonary resuscitation CPR training of healthcare workers in any setting compared to traditional training and reporting data on patients’ survival, patients’ outcomes, clinical performance and teamwork in actual or simulated resuscitation and resources needed were included. PubMed, Embase and Cochrane were searches from inception to October 28th 2024 (PROSPERO CRD42024521780). The assessment of risk of bias was done using RoB2 or ROBINS-I and the certainty of evidence was assessed by the GRADE approach. Meta-analysis was not possible due to significant heterogeneity in setting, interventions, control, and outcome definitions. The evidence was summarised according to the Synthesis Without Meta-Analysis (SwiM) reporting guidelines. No funding has been obtained. Results: From 1062 records, 10 articles were included after full-text review (4 RCTs, 6 non-randomised). The risk of bias was judged as high or some concerns for RCTs and critical or serious for non-randomised studies. The certainty of evidence was very low for all the evaluated outcomes mainly due to risk of bias, inconsistency and imprecision. Two non-randomised studies reported data on patient survival, while two other non-randomized studies provided data on the review outcome of ’patient outcomes’, suggesting a potential benefit of in situ simulation or no difference. Four non-randomised studies reported improving or no difference in clinical performance in actual resuscitation. One study reported improved teamwork in actual resuscitation while another reported no difference. Most included studies reported improved clinical performance, teamwork and CPR skill in simulated resuscitation after in situ simulation training vs. traditional training. No study evaluated the resources needed. Conclusion: The heterogenous evidence suggests that in situ simulation should be considered as an option for CPR training. The certainty of evidence is very low and cost-benefit balance is uncertain due to lack of data about resource needed.